Experimental and computational investigations of LaNi5-xAlx (x = 0, 0.25, 0.5, 0.75 and 1.0) tritium-storage alloys - Liu, Guoliang; Chen, Demin; Wang, Yuanming; Yang, Ke (Journal of materials science & technology, 2018)
Although already scientists in recent years have reported some experimental and theoretical results of La-Ni-Al series of tritium-storage alloys, several key aspects remain the subject of considerable debate. In an effort to interpret some of these unknowns, we have performed experimental and theoretical investigations for LaNi5-xAlx (x = 0, 0.25, 0.5, 0.75 and 1.0) tritium-storage alloys. Firstly, the XRD characterization indicates that the unit cell volumes of LaNi5-xAlx increase with Al content in alloys. Secondly, the PC-isotherm measurement of LaNi5-xAlx alloys shows that their hydrogen absorption/desorption plateau pressures reduce with the increase of Al content while their plateau widths narrow simultaneously. The deuterium absorption/desorption plateaus have a similar trend to hydrogen’s except for their plateaus being higher than hydrogen’s. To explain the above experimental findings, a series of calculations based on density functional theory (DFT) and frozen phonon approach have been performed. The results manifest that: (1) the partial substitutions of Al for Ni reduce the hydrogen formation energies of LaNi5-xAlxH and the number of available interstitial sites, and therefore lead to the absorption/desorption plateau pressures being reduced and the plateau widths being narrowed down at the same experimental temperatures; (2) the covalent interaction between H and Ni is an important factor for estimating the stability of LaNi5-xAlx-H system; (3) since the calculated enthalpy change ΔH is generally more accurate than the calculated entropy change ΔS with respect to the corresponding experimental value for each LaNi5-xAlx-H (or D), the curves of ΔH vs. hydrogen storage capacity instead of Van’t Hoff relation, can be used to predict the experimental plateau pressures of LaNi5-xAlx-H (D or T) at a given temperature; (4) the hydrogen isotope effect of LaNi5-xAlx-H (D or T) system can be quantitatively described as a linearity relation between ΔZPE + ΔHvib and 1/mQ (Q = H, D, T). From the good agreement between the predicted and experimental ln(PH/P0) and ln(PD/P0), it is deduced that predicting ln(PT/P0) of LaNi5-xAlxT is feasible. The procedure of pre-computing and comparing curves of ΔH vs. hydrogen storage capacity proposed in this paper provided an attractive tool to increase the efficiency of experimental alloying design of hydrogen (deuterium or tritium) storage materials.